Sildenafil Use in the Treatment of Bronchopulmonary Dysplasia-Associated Pulmonary Hypertension: A Case Series - Qasim, Amna; Dasgupta, Soham; Aly, Ashraf M.; Jain, Sunil K. (American Journal of Perinatology Reports, 2018)
Objective This article studies the role of sildenafil in reducing myocardial stress (measured by serial N-terminal pro b-type natriuretic peptide [NTproBNP] levels) secondary to bronchopulmonary dysplasia-associated pulmonary hypertension (BPD-PH).Study Design This is a case series of three extremely low birth weight infants with severe BPD at 36 weeks' postmenstrual age. All infants had very elevated NTproBNP (> 2,000 ng/dL) levels and echocardiographic evidence of BPD-PH. Sildenafil was started and infants were followed up every 2 weeks clinically along with NTproBNP levels and echocardiograms.Results After 4 weeks of sildenafil treatment, NTproBNP levels decreased significantly in all infants, echocardiograms showed significant improvement in one infant, and respiratory severity score improved significantly in one infant. All infants tolerated sildenafil.Conclusion Sildenafil reduced NTproBNP levels in all infants with BPD-PH but the echocardiographic findings and respiratory scores did not improve consistently. We speculate that this may be due to a delay in diagnosis and initiation of therapy after irreversible pulmonary changes have set in.
Keywords: bronchopulmonary dysplasia; pulmonary hypertension; pulmonary vasodilator; NTproBNP